SACRED LANDSCAPES AND URBAN EXPANSION: THE ROLE OF PAPUAN COSMOLOGY IN CITY PLANNING AND SPATIAL DEVELOPMENT - Lazarus Ramandei; Tommi (International Journal of Multidisciplinary Reseach, 2026)
This article examines the intersection of Papuan cosmological belief systems and contemporary urban planning practices in the provinces of Papua and West Papua, Indonesia. Indigenous Papuan communities maintain deep ontological relationships between sacred landscapes including mountains, rivers, forests, and ancestral sites and their social and spiritual ordering of space. As rapid urbanisation accelerates across the Bird’s Head Peninsula, the Mamberamo Basin, and the Jayapura metropolitan corridor, development frameworks frequently disregard these cosmological mappings, generating socio-cultural displacement and environmental degradation. Drawing on ethnogeographic fieldwork, spatial analysis, and a review of regional planning documents (RTRW), this study argues that integrating Papuan cosmological knowledge into city planning and spatial development policies can enhance cultural sustainability, reduce land conflict, and foster more equitable urban futures. The article advances a framework for cosmologically informed planning, proposing policy mechanisms, community consultation protocols, and spatial mapping methodologies adapted to diverse Papuan ethno-cultural contexts.